If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + x + 85 + 42 = 180 Reorder the terms: 56 + 85 + 42 + x = 180 Combine like terms: 56 + 85 = 141 141 + 42 + x = 180 Combine like terms: 141 + 42 = 183 183 + x = 180 Solving 183 + x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-183' to each side of the equation. 183 + -183 + x = 180 + -183 Combine like terms: 183 + -183 = 0 0 + x = 180 + -183 x = 180 + -183 Combine like terms: 180 + -183 = -3 x = -3 Simplifying x = -3
| 4x-5=102 | | 8-6(m-3)+4=4(m+7) | | 6x-1+11=53 | | x+-20=-16 | | F(3)=4(-5)-7 | | 9t^2-72t-54=0 | | (6x+5)(3x-4)=(2x+3)(9x-7) | | 3x-2y+5z=13 | | a^2+(a^2+4)=100 | | 3y-1+40=5x | | -6x+-18=-12 | | -(6n-4)=-7(2n+3)+3n | | 13x+7x=106 | | 3(X*5)=120 | | 13x+7s=106 | | x^2+20=8 | | 2x+2=92 | | 12/x=2/50 | | -4+f=18 | | 3x-24+15=-18 | | 50+105x=14.75x | | 3x-24+15=18 | | 3.95+3b=33.80 | | -34=v+43-5v | | 2(2x+4)=-4(x-16) | | 57.2+a*x+b*yandx+y=1 | | 2.5x+20=3x-4 | | X-11=-6 | | -2x+18=3x+33 | | 45b=25 | | (7y-8)-(5+6y)=9 | | 7=35n |